Hubungan Karakteristik Keluarga dengan Status Gizi (BB/TB) Anak Usia 6-24 Bulan di Wilayah Kerja Puskesmas Titi Papan Kota Medan - Erni Rukmana; Rasita Purba; Latifah Rahman Nurfazriah; Edy Marjuang Purba; Muhammad Edwin Fransiari (HB PRESS, 2023)
The nutritional status of children under five is an indicator of healthy growth in the community. Indicators of nutritional status of body weight according to height are to identify the poor, malnourished, good, and obese nutritional status. Nutritional status is influenced by individual and family characteristics. The purpose of this study to analyzed the relationship between family characteristics and the nutritional status of children aged 6-24 months in the working area of the Titi Papan Public Health Center, Medan City. This research method used a cross-sectional design and was carried out from June to July 2022. The sampling technique used random sampling as many as 98 children aged 6-24 months. The independent variables of this study were age, birth weight, birth length, family size, and family income. The dependent variable of this study was nutritional status based on weight according to height. Spearman test was used to determine the correlation between the independent and dependent variables. The results of the study were significant relationship of nutritional status between birth weight (p=0.04) and family size (p=0.02). The size of the family related to the growth and development of children, so it was the important information for publicity that there was relationship between family characteristics and nutritional status. Therefore, birth weight related to children nutritional status based on index of weight for height.